TRADISI KOMPANG DALAM ADAT PERNIKAHAN PADA ERA MODERNISASI DI KAMPUNG TELUK MESJID KECAMATAN SUNGAI APIT KABUPATEN SIAK - Andriko Andriko; Hambali Hambali; Haryono Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research is motivated to explain to the public about the tradition of kompang in the custom of marriage in the modernization era in Kampung Teluk Mesjid. The formulation of the problem of this research is “How is the kompang malay tradition in marriage tradition in the era of modernization in Kampung Teluk Mesjid Sungai Apit District, Siak Regency”. The purpose of this study was to determine the implementation of the kompang malay tradition in the modernization era in Kampung Teluk Mesjid Sungai Apit District, Siak Regency. Data collection techniques in this study were observation, interviews and documentation. There were 6 informants in study, namely Community Leader (1 person), Culturalists (1 person), LAM Chair (1 person), Kompang group leader (1 person), and kompang players (2 people). Data analysis techniques in this study used qualitative methods. The results in this study prove that in the tradition of kompang as a whole still uses or applies kompang culture, it’s just that the kompang tradition has changed with the modernization and advancement of the mindset of the people. The Malay community in Kampung Teluk Mesjid still preserves culture and in playing the kompang performance they still follow the methods of their predecessors, especially in malay traditional ceremonies.Key Words: The Tradition Kompang, Marriage Custom the Modernization Era